Kecemasan akademik yang dialami oleh remaja - Putri, Nazela Nanda; Daulay, Wardiyah; Marlindawani, Jenni (Holistik Jurnal Kesehatan, 2025)
Background: Academic anxiety is one of the issues often faced by teenagers, especially high school students. This anxiety can arise due to high academic demands, parental expectations, competition among students, and pressure to achieve good academic performance. Purpose: To determine academic anxiety among adolescents. Method: This quantitative descriptive study involved all 363 12th-grade students at Kutacane 1 State Senior High School in 2024. Purposive sampling was used to select 50 respondents who met the inclusion and exclusion criteria. Data collection was conducted using a questionnaire and univariate analysis. Results: Academic anxiety in adolescents was mostly categorized as severe anxiety (37 respondents (74.0%) and moderate anxiety (13 respondents (26.0%). Conclusion: The majority of respondents experienced emotional symptoms in the form of worry about learning outcomes and fear of bad grades, cognitive disorders such as confusion and doubt during exams, as well as physical manifestations in the form of sweaty hands and a pounding heart. Suggestion: Schools are expected to provide psychological support programs such as regular counseling, stress management training, and coping skills to help students manage academic anxiety, especially before exams or other important evaluation moments.   Keywords: Academic; Anxiety; Adolescents; High School Students; Academic Pressure.   Pendahuluan: Kecemasan akademik salah satu masalah yang sering dihadapi oleh remaja, terutama siswa sekolah menengah atas. Kecemasan ini dapat muncul akibat tuntutan akademik yang tinggi, ekspektasi orang tua, kompetisi antar siswa, hingga tekanan untuk meraih prestasi akademik yang baik. Tujuan: Untuk mengetahui kecemasan akademik pada remaja. Metode: Penelitian kuantitatif deskriptif dengan populasi penelitian yaitu seluruh siswa/siswi kelas XII di MAN 1 Kutacane tahun 2024 sebanyak 363 siswa/siswi. Teknik pengambilan sampel menggunakan purposive sampling dan diperoleh sebanyak 50 responden sebagai sampel, sesuai kriteria inklusi dan eksklusi. Pengambilan data menggunakan kuesioner dan analisis univariat. Hasil: Kecemasan akademik pada remaja mayoritas dalam kategori kecemasan berat sebanyak 37 responden (74.0%) dan kecemasan sedang sebanyak 13 responden (26.0%). Simpulan: Mayoritas responden mengalami gejala emosional berupa kekhawatiran terhadap hasil belajar dan ketakutan terhadap nilai buruk, gangguan kognitif seperti kebingungan dan keraguan saat ujian, serta manifestasi fisik berupa tangan berkeringat dan jantung berdebar. Saran: Pihak sekolah diharapkan dapat menyediakan program pendampingan psikologis seperti konseling rutin, pelatihan manajemen stres, dan keterampilan coping untuk membantu siswa mengelola kecemasan akademik, khususnya menjelang ujian atau momen evaluasi penting lainnya.   Kata Kunci : Akademik; Kecemasan; Remaja.